EFEKTIVITAS METODE DEBAT DALAM MENINGKATKAN KOMUNIKASI MAHASISWA PADA MATA KULIAH RETORIKA - Suarjaya, I Nyoman Alit (Samvada : Jurnal Riset Komunikasi, Media, dan Public Relation, 2023)
Communication is a vital necessity for humans. Humans are very dependent on communication, especially as social beings. In the world of education, effective communication is needed during the learning process. Besides that, the method of conveying knowledge to students must also be considered. This paper discusses the effectiveness of the debate method in improving student communication in rhetoric courses. The goal is to explore communication barriers in the learning process and find an appropriate method to overcome barriers to communication. This research uses a qualitative approach with an experimental method. The results show that the debate method is effective in providing a stimulus for students to dare to speak and express ideas and opinions in front of the class. This is expected to improve students' communication skills.